Chemical Characterization of Aerosols in a Malaysian forested area: Selai, Endau-Rompin Johor National Park - Abas, M, Radzi; Jamil Maah, Mohd; Yousef M.J. Omar, Nasr (Malaysian Journal of Science, 2005)
Atmospheric aerosols from Selai, Endau-Rompin Johor National Park were collected and their solvent-extractable organic compounds were converted to their trimethylsilyl derivatives and analyzed by gas chromatography-mass spectrometry. The principal organic compounds identified were sugar alcohols, triglycerides, fatty acids, hydrocarbons, sugars, and levoglucosan with percent compositions of 58%, 14%, 14%,6%,5%, and 3% respectively. The majority of the organic components of these forest- area aerosols is contributed by microbial sources and biomass burning.